(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In today’s world, one of the main challenges is to provide modern education to young people and thus ensure the sustainable development of the country. It is a fact that in today’s fast-paced world, learning how to access and use information has become a major goal for young people.